Performance Measurement Systems for Circular Supply Chain Management: Current State of Development - Dennis Vegter (MDPI AG, 2021)
With circular supply chain management, the need arises to measure circularity as well as economic, environmental, and social performance. This places higher demands on performance measurement systems for circular supply chain management. The current paper studies the extent to which performance measurement systems for circular supply chain management can meet these higher demands. To gain this insight, a systematic literature review is conducted. Moreover, existing definitions of circular supply chain management are reviewed and an improved definition of circular supply chain management is developed. The current paper finds, among other things, that the literature on performance measurement systems for circular supply chain management is scarce. Moreover, most of the available performance measurement systems for circular supply chain management have not been tested in practice and are therefore still in an early phase of development. Furthermore, none of the available performance measurement systems for circular supply chain management meet the requirements for effective performance measurement systems. More specifically, including interdependencies between performance measures is a requirement that none of the performance measurement systems for circular supply chain management can meet. Including interdependencies would better support the complex decision making that arises in circular supply chain management and enable one to challenge strategic assumptions about the improvement of circularity, economic, environmental, and social performance in parallel.